W-shape bright and several other solutions to the (3+1)-dimensional nonlinear evolution equations - Saliou, Youssoufa; Abbagari, Souleymanou; Houwe, Alphonse; Osman, M. S.; Yamigno, Doka Serge; Crepin, Kofane Timoleon; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
By employing the Modified Sardar Sub-Equation Method (MSEM), several solitons such as W-shape bright, dark solitons, trigonometric function solutions and singular function solutions have been obtained in two famous nonlinear evolution equations which are used to describe waves in quantum electron-positron-ion magnetoplasmas and weakly nonlinear ion-acoustic waves in a plasma. These models are the (3 + 1)-dimensional nonlinear extended quantum Zakharov-Kuznetsov (NLEQZK) equation and the (3+1)dimensional nonlinear modified Zakharov{Kuznetsov (NLmZK) equation, respectively. Comparing the obtained results with Refs. 32-34 and Refs. 43-46, additional solitonlike solutions have been retrieved and will be useful in future to explain the interaction between lower nonlinear ion-acoustic waves and the parameters of the MSEM and the obtained figures will have more physical explanation.
Keywords: Modified Sardar sub-ODE equation method; (3+1)-dimensional nonlinear extended quantum Zakharov{Kuznetsov equation; (3+1)-dimensional nonlinear modified Zakharov{Kuznetsov equation; modulation instability